Influence of Demographic Factors on Job Satisfaction of University Faculties in Nepal - Shrestha, Indira (NCC Journal, 2019)
This study is intended to examine the influence of demographic factors on job satisfaction of university faculties. One hundred and six faculty members teaching areas of management in central department of Tribhuvan University and its constituent campuses were taken as the sample. The study used survey questionnaire (23 items) derived from long form Minnesota Satisfaction Questionnaire (MSQ) (1967). The statistical tools like independent sample t-test and ANOVA were applied to find the result. The result revealed that among eight demographic variables, monthly income seemed more important variable which had significant influence on six variables (social recognition, working environment, compensation, promotion recognition and union) of job satisfaction. Furthermore, designation seemed second important demographic variable which had significant influence on five variables of job satisfaction of faculty members. Limitations of the study are identified and recommendation for the future researchers are discussed.